Robot Intelligence Technology and Applications 2012 An Edition of the Presented Papers from the 1st International Conference on Robot Intelligence Technology and Applications - Kim, Jong-Hwan.; Matson, Eric T.; Myung, Hyun.; Xu, Peter. (Advances in Intelligent Systems and Computing,, 2013)
In recent years, robots have been built based on cognitive architecture which has been developed to model human cognitive ability. The cognitive architecture can be a basis for intelligence technology to generate robot intelligence. In this edited book the robot intelligence is classified into six categories: cognitive intelligence, social intelligence, behavioral intelligence, ambient intelligence, collective intelligence and genetic intelligence. This classification categorizes the intelligence of robots based on the different aspects of awareness and the ability to act deliberately as a result of such awareness. This book aims at serving researchers and practitioners with a timely dissemination of the recent progress on robot intelligence technology and its applications, based on a collection of papers presented at the 1st International Conference on Robot Intelligence Technology and Applications (RiTA), held in Gwangju, Korea, December 16-18, 2012. For a better readability, this edition has the total 101 papers grouped into 3 chapters: Chapter I: Cognitive Intelligence, Social Intelligence and Behavioral Intelligence, Chapter II: Ambient Intelligence, Collective Intelligence and Genetic Intelligence, Chapter III: Intelligent Robot Technologies and Applications.